YMCA building at 458 Boylston Street, ca. 1883-93 - Unknown (Tufts Archival Research Center, 2005)
Street-level view of the YMCA building, located at 458 Boylston Street at the southwest corner of Boylston and Berkeley Streets. The facade of the buildings faces northwest towards Boylston Street. Two men standing at the top of the steps leading to the building's entrance are included in the photograph. Copyprint 9 1/4 x 7 1/8 Photographs